Can we look past people's race? The effect of combining race and a non-racial group affiliation on holistic processing. Issue 3 (March 2019) - Sadozai, Ayesha K; Kempen, Kate; Tredoux, Colin; Robbins, Rachel A
Face memory is worse for races other than one's own, in part because other-race faces are less holistically processed. Both experiential factors and social factors have been suggested as reasons for this other-race effect . Direct measures of holistic processing for race and a non-racial category in faces have never been employed, making it difficult to establish how experience and group membership interact. This study is the first to directly explore holistic processing of own-race and other-race faces, also classed by a non-racial category (university affiliation). Using a crossover design, White undergraduates (in Australia) completed the part-whole task for White (American) and Black South African faces attributed to the University of Western Sydney (own) and University of Sydney (other). Black South African undergraduates completed the same task for White and Black South African faces attributed to the University of Cape Town (own) and Stellenbosch University (other). It was hypothesised that own-race faces would be processed more holistically than other-race faces and that own-university faces would be processed more holistically than other-university faces. Results showed a significant effect of race for White participants (White faces were matched more accurately than Black faces), and wholes were matched more accurately than parts, suggesting holistic processing, but only for White faces. No effect of university was found. Black South African participants, who have more experience with other-race faces, processed wholes better than parts irrespective of race and university category. Overall, results suggest that experiential factors of race outweigh any effects of a non-racial shared group membership. The quality of experience for the named populations, stimuli presentation, and degree of individuation are discussed.